Air Pollution and Interstitial Lung Disease - Yong Suk Jo; Jin Woo Song (Tuberculosis and Respiratory Diseases)
This review article explores the multifaceted relationship between air pollution and interstitial lung diseases (ILDs), particularly focusing on idiopathic pulmonary fibrosis, the most severe form of fibrotic ILD. Air pollutants are mainly composed of particulate matter, ozone (O3), nitrogen dioxide (NO2), carbon monoxide (CO), and sulfur dioxide (SO2). They are recognized as risk factors for several respiratory diseases. However, their specific effects on ILDs and related mechanisms have not been thoroughly studied yet. Emerging evidence suggests that air pollutants may contribute to the development and acute exacerbation of ILDs. Longitudinal studies have indicated that air pollution can adversely affect the prognosis of disease by decreasing lung function and increasing mortality. Lots of in vitro, in vivo , and epidemiologic studies have proposed possible mechanisms linking ILDs to air pollution, including inflammation and oxidative stress induced by exposure to air pollutants, which may induce mitochondrial dysfunction, promote cellular senescence, and disrupt normal epithelial repair processes. Despite these findings, effective interventions to mitigate effects of air pollution on ILD are not well established yet. This review emphasizes the urgent need to address air pollution as a key environmental risk factor for ILDs and calls for further studies to clarify its effects and develop preventive and therapeutic strategies.